Nanocrystal/Metal–Organic Framework Hybrids as Electrocatalytic Platforms for CO2 Conversion. (2nd August 2019) - Guntern, Yannick T.; Pankhurst, James R.; Vávra, Jan; Mensi, Mounir; Mantella, Valeria; Schouwink, Pascal; Buonsanti, Raffaella
Abstract: The tunable chemistry linked to the organic/inorganic components in colloidal nanocrystals (NCs) and metal–organic frameworks (MOFs) offers a rich playground to advance the fundamental understanding of materials design for various applications. Herein, we combine these two classes of materials by synthesizing NC/MOF hybrids comprising Ag NCs that are in intimate contact with Al‐PMOF ([Al2 (OH)2 (TCPP)]) (tetrakis(4‐carboxyphenyl)porphyrin (TCPP)), to form Ag@Al‐PMOF. In our hybrids, the NCs are embedded in the MOF while still preserving electrical contact with a conductive substrate. This key feature allows the investigation of the Ag@Al‐PMOFs as electrocatalysts for the CO2 reduction reaction (CO2 RR). We show that the pristine interface between the NCs and the MOFs accounts for electronic changes in the Ag, which suppress the hydrogen evolution reaction (HER) and promote the CO2 RR. We also demonstrate a minor contribution of mass‐transfer effects imposed by the porous MOF layer under the chosen testing conditions. Furthermore, we find an increased morphological stability of the Ag NCs when combined with the Al‐PMOF. The synthesis method is general and applicable to other metal NCs, thus revealing a new way to think about rationally tailored electrocatalytic materials to steer selectivity and improve stability. Abstract : Feinabstimmung der Reaktivität : MOF/Nanokristall‐Hybride begünstigen die CO2 ‐Reduktion, unterdrücken die Wasserstoffentwicklung und verbessern die katalytische Stabilität. Synthesedesign ist essenziell für die Erforschung dieser Multikomponenten‐Elektrokatalysatoren.